Reconsidering the wholesale food market - Sarah Elton; Matilda Dipieri; Donald Cole (Journal of Agriculture, Food Systems, and Community Development)
The wholesale food terminal, public infrastructure that connects farmers with wholesale intermediaries, largely has been superseded in North America by major supermarkets and their private supply chains. Yet the Ontario Food Terminal, Canada’s largest wholesale food terminal and the third largest on the continent, continues to play a key role in Toronto. Drawing on field and archival data in our case study of this public institution, we argue that the wholesale food market supports a diverse retail foodscape that widens food access in Toronto. Further, it provides a reliable marketplace for Ontario produce farmers, thus supporting both agriculture of the middle in the region as well as retail of the middle. We demonstrate how the wholesale food market can contribute to territorial food systems and should be considered as an institutional component of circular food economies.